Quality of life, lower urinary tract function and sexual health after sex reassignment surgery in male to female transexuals (2016)
The aim of this study is to thoroughly report on surgical outcomes, quality of life (QoL), lower urinary tract function, sexual health and sexual desire from four patients who underwent male to female (MTF) sex reassignment surgery (SRS) using the Sava Pe